Analysis of the Implementation of Usaha Kesehatan Sekolah (UKS-School Health Program) in Improving the Holistic Health of Elementary School Students in Siwalan District - Heri Susilo; Agus Rahardjo (Universitas Negeri Semarang, 2026)
School health programs play a crucial role in supporting students' holistic health development during elementary school age, which is a critical period for habit formation that will persist into adulthood. The implementation of Usaha Kesehatan Sekolah (UKS—School Health Program) in Siwalan District, a coastal region in Pekalongan Regency, Central Java, demonstrates considerable variation across schools due to differences in infrastructure, management commitment, and external support systems. This study aims to analyze the strategic role of UKS in enhancing students' holistic health through a comprehensive SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Using qualitative methodology, data were collected through observations, semi-structured interviews with 42 informants across 10 elementary schools, and documentation of school health programs and administration. Findings reveal that while some schools demonstrate strong school leadership commitment, PHBS (Perilaku Hidup Bersih dan Sehat—Healthy Living Behavior) culture, and active health center support, most schools face significant limitations in health facilities, qualified UKS spaces, teacher competence, and structured health administration. Opportunities for strengthening UKS exist through government health policies, health center partnerships, community involvement, and digital media utilization for health education, though these are challenged by environmental threats such as coastal flooding, inadequate food safety awareness, and budget constraints. The study contributes to school health science by demonstrating that effective UKS implementation requires integrated SO, WO, ST, and WT strategies combining human resource training, facility development, administrative strengthening, and multisectoral collaboration among schools, health centers, local government, and communities.